Comparative study of 1064 nm nanosecond, 1064 nm picosecond, 755 nm, and 595 nm lasers for tattoo removal: An essential role by macrophage. Issue 5 (15th March 2022) - Du, Xiao‐Jie; Zhou, Hong‐Mei; Wang, Zhao; Liu, Jing; Wang, Jia‐Feng; Li, Dong; Wu, Ting‐Ting; Chen, Bin; Zeng, Wei‐Hui
Abstract: Objectives: Tattoo removal is in high demand, and many types of lasers can be used for tattoo removal. Macrophages play an important role in the persistence of tattoos. However, comparative studies of the efficacy of tattoo removal with different lasers versus the relationship between the destruction of pigment particles or recruitment of macrophages after laser treatment are lacking. Materials and Methods: Tattoo models were established on the rat dorsal surface and randomly treated with 1064 nm nanosecond, 1064 nm picosecond, 755 nm, and 595 nm lasers for one session. Clinical photographic evaluation, melanin index, hematoxylin and eosin staining, identification of macrophages by CD68 staining, and transmission electron microscopy were conducted at different time points. Results: Regardless of the pulse duration, all lasers included were effective for the removal of black tattoos, with 1064 nm lasers having the best efficacy, followed by 755 and 595 nm lasers. The diameter of the pigment particles and recruitment of dermal macrophages correlated with the efficacy of tattoo removal. Conclusions: In this study, the 1064 nm lasers were found to be the most effective for black tattoo removal. However, there was no significant difference between the 1064 nm picosecond and the nanosecond lasers. Macrophage recruitment plays an essential role in pigment metabolism during laser‐tattoo removal.